A novel promising laccase from the psychrotolerant and halotolerant Antarctic marine Halomonas sp. M68 strain - Bisaccia, Melissa; Binda, Elisa; Rosini, Elena; Caruso, Gabriella; Dell'Acqua, Ombretta; Azzaro, Maurizio; Laganà, Pasqualina; Tedeschi, Gabriella; Maffioli, Elisa M.; Pollegioni, Loredano; Marinelli, Flavia (Frontiers in Microbiology, 2023)
Microbial communities inhabiting the Antarctic Ocean show psychrophilic and halophilic adaptations conferring interesting properties to the enzymes they produce, which could be exploited in biotechnology and bioremediation processes. Use of cold- and salt-tolerant enzymes allows to limit costs, reduce contaminations, and minimize pretreatment steps. Here, we report on the screening of 186 morphologically diverse microorganisms isolated from marine biofilm and water samples collected in Terra Nova Bay (Ross Sea, Antarctica) for the identification of new laccase activities. After primary screening, 13.4% and 10.8% of the isolates were identified for the ability to oxidize 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and the dye azure B, respectively. Amongst them, the marine Halomonas sp. strain M68 showed the highest activity. Production of its laccase-like activity increased six-fold when copper was added to culture medium. Enzymatic activity guided separation coupled with mass spectrometry identified this intracellular laccase-like protein (named Ant laccase) as belonging to the copper resistance system multicopper oxidase family. Ant laccase oxidized ABTS and 2,6-dimethoxy phenol, working better at acid pHs. The enzyme showed a good thermostability, with optimal temperature in the 40-50 °C range and maintaining more than 40% of its maximal activity even at 10 °C. Furthermore, Ant laccase was salt- and organic solvent-tolerant, paving the way for its use in harsh conditions. To our knowledge, this is the first report concerning the characterization of a thermo- and halo-tolerant laccase isolated from a marine Antarctic bacterium.